Irritable bowel syndrome in midlife women: a narrative review - Pei-Lin Yang; Margaret M. Heitkemper; Kendra J. Kamp (BMC, 2021)
Abstract Midlife women between the ages of 40 and 65 years have reported multiple challenges due to menopausal, developmental, and situational transitions from younger to older adulthood. During the midlife period, many women seek health care for gastrointestinal symptoms and irritable bowel syndrome (IBS). Multiple factors including stress, poor sleep, diet, and physical inactivity may contribute to IBS or gastrointestinal symptoms in midlife women. As such, a comprehensive assessment and treatment approach is needed for midlife women suffering gastrointestinal symptoms. This article reviews the main aspects of the menopausal transition, sex hormonal changes, abdominal and pelvic surgery, psychosocial distress, behavioral factors, and gut microbiome, as well as their relevance on IBS and gastrointestinal symptoms in midlife women. Also, management strategies for IBS in midlife women are discussed. To date, gastrointestinal symptoms during midlife years remain a critical area of women's health. Additional research is needed to better understand the contributors to gastrointestinal symptoms in this group. Such efforts may provide a new window to refine or develop treatments of gastrointestinal symptoms for midlife women.